Subcutaneous Benign Fibrous Histiocytoma: Rare Presentation on Cheek—Case Report and Review of Literature - Srikanth, Damera (J Maxillofac Oral Surg, 2015)
Fibrous histiocytoma is a benign tumor of mesenchymal origin. The tumor frequently appears in sun exposed areas on skin and orbital tissues. The subcutaneous appearance of this tumor in deep soft tissues is rare. We present here the eighth reported case of subcutaneous benign fibrohistiocytoma in a 27 year old male patient. Histopathology of the tumor comprises fibroblastic and histiocytic cells which mimic dermatofibroma, xanthomas and nodular fasciitis. Special stains like vimentin can only differentiate these tumors.